P120 A collaborative approach to rolling out advice and guidance. (23rd April 2022) - MacPhie, Elizabeth; Horton, Sarah; Madan, Ayesha; Rao, Chandini; Fish, Sarah
Abstract: Background/Aims: Advice and Guidance (A&G) is a key priority for out-patient transformation, provides primary care with an immediate specialist opinion and negates patients waiting several months to see a specialist in clinic. During the last year we have taken incremental steps to embed and promote A&G. The importance of seeking the views of primary care colleagues has been paramount to increasing engagement and understand any unintended consequences. Methods: A&G was switched on through e-Referral Service in July 2019. Information was provided as to what was appropriate for A&G. In December 2020 an alternative A&G system was rolled out providing an opportunity to promote the use of A&G and we started to redirect appropriate referrals at triage. In July 2021, we took a further step to return referrals where appropriate with an immediate specialist opinion. Both A&G systems record activity and a spreadsheet is kept of all triage outcomes. The new A&G system collects feedback from primary care. There have been regular opportunities to speak to primary care colleagues. Results: During the first year of implementation of A&G we received on average three queries a week. Following the roll-out of the new A&G system we saw a steady rise in the number of queries. In April to June 2021, received 56 direct A&G queries. Of 669 referrals received, 33 were redirected to A&G. In July to September 2021, we received 58 direct A&G queries. Of 549 referrals received, 12 were redirected to A&G and 19 were returned with immediate advice. Routine waiting times have reduced from 12 to 7 weeks over the last 12 months. Feedback from primary care regarding 169 A&G queries has been very positive with 98% finding advice helpful. In partnership with the CCG we have developed a Top Tips Guide for Primary Care and delivered an evening workshop to promote the use of A&G. Feedback from GPs resulted in a letter being sent to patients when we respond to a referral with immediate advice and a leaflet is being developed to help patients understand the triage process and the different means by which a specialist opinion may be provided. Conclusion: A&G has most importantly provided patients with an immediate specialist opinion and reduced the waiting times for those patients who still need to be assessed in clinic. Small incremental changes have allowed the team to appropriately job plan the workload and colleagues in primary care adapt to a new way of working. Regular discussions with primary care have helped understand any frustrations and to adopt a solution-focused approach. We recognise the importance of involving patients in the discussion, supporting them to understand an alternative way of working and change their mind-set on how specialist advice can be delivered. Disclosure: E. MacPhie: Other; EM is the secretary of the North West Rheumatology Club, meetings have been supported by UCB, MSD, Abbvie and Lilly. S. Horton: None. A. Madan: None. C. Rao: None. S. Fish: None.